Distributed manufacturing: scope, challenges and opportunities - Singh Srai, Jagjit; Kumar, Mukesh; Graham, Gary; Phillips, Wendy; Tooze, James; Ford, Simon; Beecher, Paul; Raj, Baldev; Gregory, Mike; Kumar Tiwari, Manoj; Ravi, B.; Neely, Andrew; et al. (Taylor & Francis, 2016)
This discussion paper aims to set out the key challenges and opportunities emerging from distributed manufacturing (DM). We begin by describing the concept, available definitions and consider its evolution where recent production technology developments (such as additive and continuous production process technologies), digitisation together with infrastructural developments (in terms of IoT and big data) provide new opportunities. To further explore the evolving nature of DM, the authors, each of whom are involved in specific applications of DM research, examine through an expert panel workshop environment emerging DM applications involving new production and supporting infrastructural technologies. This paper presents these generalisable findings on DM challenges and opportunities in terms of products, enabling production technologies and the impact on the wider production and industrial system. Industry structure and location of activities are examined in terms of the democratising impact on participating network actors. The paper concludes with a discussion on the changing nature of manufacturing as a result of DM, from the traditional centralised, large-scale, long lead-time forecast-driven production operations to a new DM paradigm where manufacturing is a decentralised, autonomous near end user-driven activity. A forward research agenda is proposed that considers the impact of DM on the industrial and urban landscape.
Keywords: Distributed manufacturing; Emerging production technologies; ICT; Digitisation; Localisation; Personalisation community-based production; Urban environments; Smart city production systems